2004
DOI: 10.1111/j.1349-7006.2004.tb03224.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed molecules in adult T‐cell leukemia cells proliferating in vivo

Abstract: HTLV-I is the causative agent of adult T-cell leukemia (ATL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…These ideas are consistent with the long latency until the onset of ATL, its relatively low incidence (Tajima, 1990), and mono-or oligoclonal growth of leukemic cells. As a result, certain genes regulated by NF-kB are differentially expressed in freshly isolated primary leukemic cells and Tax-positive T-cell lines (Koga et al, 2004;Sasaki et al, 2005). For instance, OX40 ligand, or gp34, is strongly expressed in Tax-positive HTLV-I-transformed cells (Miura et al, 1991), but cannot be found in primary ATL cells (Imura et al, 1997).…”
Section: Loss Of Viral Gene Expression In the Late Stages Of Atl Leukmentioning
confidence: 99%
See 1 more Smart Citation
“…These ideas are consistent with the long latency until the onset of ATL, its relatively low incidence (Tajima, 1990), and mono-or oligoclonal growth of leukemic cells. As a result, certain genes regulated by NF-kB are differentially expressed in freshly isolated primary leukemic cells and Tax-positive T-cell lines (Koga et al, 2004;Sasaki et al, 2005). For instance, OX40 ligand, or gp34, is strongly expressed in Tax-positive HTLV-I-transformed cells (Miura et al, 1991), but cannot be found in primary ATL cells (Imura et al, 1997).…”
Section: Loss Of Viral Gene Expression In the Late Stages Of Atl Leukmentioning
confidence: 99%
“…Early studies demonstrate that HTLV-I infection promotes the expression of various cytokines and their receptors, most notably the T-cell growth factor interleukin-2 (IL-2) (Maruyama et al, 1987;Siekevitz et al, 1987) and the a subunit of its high-affinity receptor complex (IL-2Ra) (Inoue et al, 1986;Cross et al, 1987;Siekevitz et al, 1987). More recent gene array analyses reveal the abnormal expression of a large number of additional genes associated with HTLV-I-induced T-cell transformation (Harhaj et al, 1999a;de La Fuente et al, 2000;Pise-Masison et al, 2002;Koga et al, 2004;Sasaki et al, 2005). Among these genes are those encoding cytokines and cytokine receptors, apoptosis inhibitors, cell cycle regulators, immune receptors that belong to the tumor necrosis factor receptor (TNFR) family, transcription factors, and intracellular signaling molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of HTLV-I mRNA in this cell line was undetectable by Northern blot or reverse-transcription polymerase chain reaction (RT-PCR) analysis (Imada et al, 1995). ATL-43T (Nosaka et al, 2000) and SYK-11L(+) (Koga et al, 2004) are IL-2-dependent T-cell lines of leukaemic cell origin established from ATL patients. SY (Imada et al, 1995) and MT-2 are HTLV-I-infected T-cell lines.…”
Section: Cell Linesmentioning
confidence: 99%
“…Tax represses the activity of proteins or expression of genes such the DNA b polymerase which is a DNA repair enzyme involved in base excision repair (Jeang et al, 1990), DNA topoisomerase I Yoshida and Suzuki, 2000), TGFb1 (Arnulf et al, 2002;Lee et al, 2002;Mori et al, 2001b), and the apoptosis-accelerating gene bax . Microarrays have recently confirmed much of this data by comparing HTLV-1-infected and uninfected peripheral blood mononuclear cells (PBMCs) Kohno et al, 2000), the HTLV-1þ C8166 T-cell line with the uninfected CEM cell line (de La Fuente et al, 2000), normal PBMCs with several HTLV-1þ cell lines (Affymetrix GeneChip) (Pise-Masison et al, 2002), an inducible Tax-expressing JurkaT-cell line (NIH Oncochip) (Ng et al, 2001); and fresh ATL cells from acute and chronic patients (Koga et al, 2004;Tsukasaki et al, 2004). The expression of growth-inducing factors, particularly the cytokines and the cytokine receptors, suggests that autocrine and/or paracrine mechanisms are involved in T-cell proliferation in ATL patients.…”
Section: Modulation Of Host Gene Expression Andmentioning
confidence: 66%